Improving Elementary School Students’ Critical Thinking Skill in Science through HOTS-based Science Questions: A Quasi-Experimental Study (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
There have been many efforts to improve elementary school students’ critical thinking skills in science through various learning methods. However, only a few research results show efforts to improve critical thinking skills through HOTS-based science questions for elementary school students. Therefore, the purpose of this study is to test the effectiveness of student habituation with HOTS-based science questions in improving elementary school students’ critical thinking skills in science. Quasi-experimental methods were employed in this research with a nonequivalent control group design involving a treatment class and a control class. The treatment class gets treatment in HOTS-based science questions habituation during the learning process, while the control class in conventional approaches. A total of 60 students is from one of the elementary schools in Surakarta, Indonesia. To take data related to students’ critical thinking skills, they were given pretest and posttest where each test used HOTS-based science questions in an essay. The obtained data from the tests were then analyzed using descriptive and inferential statistical techniques. This study showed that the average of critical thinking skills in science of students in the experimental class was higher than the control class, with a positive mean difference of 0.4226. Based on these results, it is recommended that the results of this study can provide an overview to educational practitioners at the elementary school level and researchers in the field of science education related to efforts to improve elementary school students’ critical thinking skills in science through the habituation of HOTS-based science questions.